2024
DOI: 10.1038/s42003-023-05536-0
|View full text |Cite
|
Sign up to set email alerts
|

A diversity of novel type-2 innate lymphoid cell subpopulations revealed during tumour expansion

Clara Wenjing Xia,
Iryna Saranchova,
Pablo L. Finkel
et al.

Abstract: Type 2 innate lymphoid cells (ILC2s) perform vital functions in orchestrating humoral immune responses, facilitating tissue remodelling, and ensuring tissue homeostasis. Additionally, in a role that has garnered considerably less attention, ILC2s can also enhance Th1-related cytolytic T lymphocyte immune responses against tumours. Studies have thus far generally failed to address the mystery of how one ILC2 cell-type can participate in a multiplicity of functions. Here we utilized single cell RNA sequencing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 98 publications
(158 reference statements)
1
2
0
Order By: Relevance
“…This scarcity of infiltrating immune cells in the untreated tumors indicated a limited immune response within the tumor microenvironment. In stark contrast, in the tumors of animals which underwent ADT treatment using activated tILC2 cells, we detected a significantly higher number of leukocytes within the tumor tissue, as illustrated in Figures 5C-K, and it is well in line with our data provided in Xia et al regarding the enhanced T cells recruitment abilities in activated tILC2s (39). This influx of CD8 + , CD4 + T lymphocytes and eosinophils suggested a robust enrichment of both innate and adaptive immune response against the tumor cells in the treated animals.…”
Section: Adoptive Transfer Of Tilc2s Can Improve the Overall Survival...supporting
confidence: 92%
See 2 more Smart Citations
“…This scarcity of infiltrating immune cells in the untreated tumors indicated a limited immune response within the tumor microenvironment. In stark contrast, in the tumors of animals which underwent ADT treatment using activated tILC2 cells, we detected a significantly higher number of leukocytes within the tumor tissue, as illustrated in Figures 5C-K, and it is well in line with our data provided in Xia et al regarding the enhanced T cells recruitment abilities in activated tILC2s (39). This influx of CD8 + , CD4 + T lymphocytes and eosinophils suggested a robust enrichment of both innate and adaptive immune response against the tumor cells in the treated animals.…”
Section: Adoptive Transfer Of Tilc2s Can Improve the Overall Survival...supporting
confidence: 92%
“…Our previous study (39) demonstrated the ILC2-plasticity during tumor progression on scRNA level, as an acquisition of the new type-1-like immune functions. In the current study, we provide the analysis a set of 32 cytokines and chemokines proteins secreted by tILC2s during neoplasm development, when compared to the protein profile of nILC2 cells.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation